Successful treatment of isolated venous malformation with 1444-nm fiberoptic Nd-YAG laser. (17th February 2016) - Radmanesh, Mohammad; Radmanesh, Ramin
Abstract : Two patients with isolated venous malformations on the face were treated with fiberoptic Nd-YAG laser (Lutronic laser company, South Korea). After nerve block anesthesia, the laser tip was pushed into the lesions either through a hole made by a 16 gauge needle or directly by inserting and triggering the laser tip few millimeters away from the lesions. The laser tip was pushed from one or few directions and moved back and forth, while triggering, in a fan pattern to cover the whole lesion. The procedure was continued till complete flattening of the lesions. The parameters used were pulse rate = 30 hertz, pulse energy = 300 mJoules, power = 6.0 watt, and total energy used for the first patient was 1000 Joules and for the second patient was 800 joules.Results: The lesions flattened completely after whole tissue coagulation. Moderate redness disappeared in the first 48 hours. No persistent discoloration and no sign of cutaneous burning appeared after the procedures. No antibiotic or analgesic was prescribed after the procedure. The patients were followed for more than 2 years with no recurrence and good cosmetic results.Conclusion: The fiberoptic Nd-YAG laser can be used as an effective procedure for venous malformations.